Ribosomal protein gene RPL9 variants can differentially impair ribosome function and cellular metabolism. Issue 2 (4th December 2019) - Lezzerini, Marco; Penzo, Marianna; O'Donohue, Marie-Françoise; Marques dos Santos Vieira, Carolina; Saby, Manon; Elfrink, Hyung L; Diets, Illja J; Hesse, Anne-Marie; Couté, Yohann; Gastou, Marc; Nin-Velez, Alexandra; Nikkels, Peter G J; et al.
Abstract: Variants in ribosomal protein (RP) genes drive Diamond-Blackfan anemia (DBA), a bone marrow failure syndrome that can also predispose individuals to cancer. Inherited and sporadic RP gene variants are also linked to a variety of phenotypes, including malignancy, in individuals with no anemia. Here we report an individual diagnosed with DBA carrying a variant in the 5′UTR of RPL9 (uL6). Additionally, we report two individuals from a family with multiple cancer incidences carrying a RPL9 missense variant. Analysis of cells from these individuals reveals that despite the variants both driving pre-rRNA processing defects and 80S monosome reduction, the downstream effects are remarkably different. Cells carrying the 5′UTR variant stabilize TP53 and impair the growth and differentiation of erythroid cells. In contrast, ribosomes incorporating the missense variant erroneously read through UAG and UGA stop codons of mRNAs. Metabolic profiles of cells carrying the 5′UTR variant reveal an increased metabolism of amino acids and a switch from glycolysis to gluconeogenesis while those of cells carrying the missense variant reveal a depletion of nucleotide pools. These findings indicate that variants in the same RP gene can drive similar ribosome biogenesis defects yet still have markedly different downstream consequences and clinical impacts.